The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1145/359642.359654
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing constraint expressions

Abstract: A constraint network representation is presented for a combinatorial search problem: finding values for a set of variables subject to a set of constraints. A theory of consistency levels in such networks is formulated, which is related to problems of backtrack tree search efficiency. An algorithm is developed that can achieve any level of consistency desired, in order to preprocess the problem for subsequent backtrack search, or to function as an alternative to backtrack search by explicitly determining all so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
144
0
7

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(152 citation statements)
references
References 12 publications
1
144
0
7
Order By: Relevance
“…It can be shown that the above consistency techniques are covered by a general notion of (strong) k-consistency [66]. Indeed, NC is equivalent to strong 1-consistency, AC to strong 2-consistency, and PC to strong 3-consistency.…”
Section: Consistency Techniquesmentioning
confidence: 99%
“…It can be shown that the above consistency techniques are covered by a general notion of (strong) k-consistency [66]. Indeed, NC is equivalent to strong 1-consistency, AC to strong 2-consistency, and PC to strong 3-consistency.…”
Section: Consistency Techniquesmentioning
confidence: 99%
“…All above mentioned consistency techniques are covered by a general notion of k-consistency [39] and strong k-consistency. A constraint graph is k-consistent if for every system of values for k − 1 variables satisfying all the constraints among these variables, there exist a value for arbitrary k-th variable such that the constraints among all k variables are satisfied.…”
Section: Csp Solving -Consistency Techniquesmentioning
confidence: 99%
“…Path-consistency is equivalent to 3-consistency [88] which holds if for every consistent instantiation of two variables it is always possible to find an instantiation for any third variable such that the three variables together are consistent. 3-consistency can be generalised to k-consistency which holds if for any consistent instantiation of k − 1 variables there is always a consistent instantiation for any kth variable.…”
Section: Constraint-based Spatial Reasoningmentioning
confidence: 99%